Advance of transanal opening of intersphincteric space in the treatment of complex anal fistula - Chen Zeyang; Cai Mingzhu; Bai Zhaofu; Pan Shaorong; Li Yalun; Wang Pengyuan; Fang Jingjing; Sun Guidong; Shao Wanjin (结直肠肛门外科)
Patients with complex anal fistula experience recurrent perianal ulceration and infection, which seriously affects their quality of life. Due to the difficulty of treatment, surgeons need to weigh how to improve the success rate of surgery while reducing the risk of postoperative fecal incontinence. In recent years, transanal opening of intersphincteric space (TROPIS) has gradually been applied to the treatment of complex anal fistula as a sphincter-preserving surgical approach. This article will review the theoretical basis and operational procedures, effectiveness and safety, and application scope of TROPIS in the treatment of complex anal fistula, aiming to provide a reference for the treatment of complex anal fistula.